IDENTIFICATION AND CHARACTERIZATION OF CARMOVIRUS ON CARNATION (Dianthus caryophyllus L.) IN WEST JAVA, INDONESIA - Erniawati Diningsih; Gede Suastika; Tri Asmira Damayanti; Slamet Susanto (AGRIVITA, Journal of Agricultural Science, 2015)
Carnation has a highly economic demand of cut flower in Indonesia.  Field observations in West Java Indonesia was conducted in order to find the typical mottle symptoms that was a suspect caused by a virus disease. Identification of the virus was respectively conducted by performing ELISA test with four anti sera and characterizations held by bioassay, observing of virion particles, detecting of nucleic acid by RT-PCR and nucleotide sequencing. Total of 403 samples were collected from plants with or no virus-like symptoms. Among those all tested, 83% were found to be infected by Carnation mottle virus (CarMV), but negatively against Carnation ringspot virus (CRSV), Carnation laten virus (CLV), and Carnation vein mottle virus (CVMV) antisera. By mechanical inoculation, the virus was able to infect systemically Cenopodium quinoa and locally infect on others. However on Phalaenopsis sp and Gomprena globosa, there was symptompless found. The isometric CarMV particles size was approximately 30 nm. RT-PCR using specific primers of CP gene of CarMV successfully amplified a DNA sized 1000 bp.  CarMV West Java Indonesian (Idn-WJ) isolates possessed the highest nucleotide and amino acid homology with CarMV from Spain and was in the same cluster with CarMV from China, Taiwan and Israel.